Pneumococcal conjugate vaccine effectiveness against hypoxemia in children with suspected pneumonia in Kenya; analysis from a real-world sentinel surveillance platform - Fredrick Mutisya; George O. Agogo; Jared Opudo; Barbara Jepkorir; Athman Mwatondo; Daniel Langat; Peninah Munyua; Duncan Chege; Jonas Z. Hines (PLoS ONE, 2026)
The 10-valent pneumococcal conjugate vaccine (PCV-10) has reduced the burden of pneumococcal disease in children. Integrated facility-based sentinel surveillance (IFBS) monitors a range of common causes of febrile illnesses in Kenya. We used this system to assess the real-world vaccine effectiveness (VE) of PCV-10 against hypoxemia among children with suspected pneumonia in Kenya. We analysed IFBS data collected from 13 sites across Kenya from 2017 to 2024. We included children aged 6 weeks to 59 months with reported fever or temperature ≥38.0°C, respiratory features consistent with suspected pneumonia, and a copy of their vaccination records (i.e., child health booklet). We excluded children with a positive test result indicating a non-Pneumococcal aetiology (i.e., positive result on a multiplex PCR, malaria microscopy or rapid diagnostic test, or SARS-CoV-2 PCR). We assessed the association of vaccination status with hypoxemia, defined as an oxygen saturation of ≤90%, adjusting for age, sex, and year. VE was calculated as 1 minus the odds ratio of hypoxemia among children with suspected pneumonia calculated using generalized estimating equations to account for clustering by site. Overall, 3,533 children were analysed, with 94% being up to date with PCV-10 vaccination. The median patient age was 11 months (interquartile range: 6–17). Hypoxemia was observed in 37% of fully vaccinated children, 41% in partially vaccinated children, and 52% in unvaccinated children (χ² test, p = 0.03). The adjusted VE for full vaccination against hypoxemia in children with suspected pneumonia was 39% (95% confidence interval: 6–61%). Among children with suspected pneumonia in Kenya, PCV-10 vaccination was associated with reduced hypoxemia. The PCV-10 coverage in this dataset was high, potentially reflecting a robust routine vaccination effort since PCV-10 was introduced in Kenya in 2011. High-quality surveillance data can be used to provide real-world evidence to support routine immunization programs.